Anti Proliferative and Pro Apoptotic Effects of Flavonoid Quercetin Are Mediated by CB1 Receptor in Human Colon Cancer Cell Lines. Issue 12 (24th August 2015) - Refolo, Maria Grazia; D'Alessandro, Rosalba; Malerba, Natascia; Laezza, Chiara; Bifulco, Maurizio; Messa, Caterina; Caruso, Maria Gabriella; Notarnicola, Maria; Tutino, Valeria
<x xml:space="preserve">Abstract</x> Quercetin, the major constituent of flavonoid and widely present in fruits and vegetables, is an attractive compound for cancer prevention due to its beneficial anti proliferative effects, showing a crucial role in the regulation of apoptosis and cell cycle signaling. In vitro studies have demonstrated that quercetin specifically influences colon cancer cell proliferation. Our experiments, using human colon adenocarcinoma cells, confirmed the anti proliferative effect of quercetin and gave intriguing new insight in to the knowledge of the mechanisms involved. We observed a significant increase in the expression of the endocannabinoids receptor (CB1‐R) after quercetin treatment. CB1‐R can be considered an estrogen responsive receptor and quercetin, having a structure similar to that of the estrogens, can interact with CB1‐R leading to the regulation of cell growth. In order to clarify the contribution of the CB1‐R to the quercetin action, we investigated some of the principal molecular pathways that are inhibited or activated by this natural compound. In particular we detected the inhibition of the major survival signals like the PI3K/Akt/mTOR and an induction of the pro apoptotic JNK/JUN pathways. Interestingly, the metabolism of β‐catenin was modified by flavonoid both directly and through activated CB1‐R. In all the experiments done, the quercetin action has proven to be reinforced by anandamide (Met‐F‐AEA), a CB1‐R agonist, and partially counteracted by SR141716, a CB1‐R antagonist. These findings open new perspectives for anticancer therapeutic strategies. J. Cell. Physiol. 230: 2973–2980, 2015. © 2015 Wiley Periodicals, Inc.